BSC inside a strategic management control package. Issue 1 (3rd May 2019) - Bénet, Nathalie; Deville, Aude; Naro, Gerald
Abstract : Purpose: Kaplan and Norton proposed the strategy map as a way to overcome the weaknesses of the balanced scorecard (BSC), but this approach may not be enough. The purpose of this paper is to present a strategic management control package composed of three systems from strategic management and management control. This conceptual approach operationalizes strategic alignment, which is the core interest of the BSC. Design/methodology/approach: The rationale for this research is derived from the literatures on business models (BMs), the BSC and management control packages. The authors first identified gaps in the BSC literature, which has underlined the BSC's insufficient connection to strategy, and the strategic literature, which has criticized the BM as being too conceptual. The authors propose to fill these gaps through contributions from the management control package literature. Findings: The findings are in line with the current literature on the interdependencies of management control systems. In response to the criticism of the BSC because of its weak strategic foundations, the authors provide a framework comprising three management systems: the BM, the strategy map and the BSC. This framework ultimately promotes two feedback loops that provide a dynamic view of the reciprocal influences of the BSC and strategy. Research limitations/implications: Several authors note that the BSC suffers from a lack of conceptualization. The underlying assumptions and the conceptual and empirical validity of the cause-and-effect relationships are particularly questioned. Therefore, the purpose of this paper is to overcome the criticism linked to the "low" strategic alignment of the strategy map, and then of the BSC, by proposing a conceptual framework based on a package including three management systems: the BSC, the strategy map and the BM. A major limit lies in the purely conceptual dimension of this research, and it will be interesting to empirically investigate the conceptual package through longitudinal case studies. Practical implications: The authors propose guidelines to develop a strategically aligned BSC through a three-step operationalization process to achieve a non-linear strategic management control. Moreover, the authors suggest empirical research avenues to address the weaknesses of Kaplan and Norton's BSC and to enhance its connection to strategy through an integrated strategic management control package that includes a BM. Originality/value: This paper adds value by proposing a package of management systems that includes both strategic management and management control perspectives. The authors, therefore, offer a way to bridge the gap between these research streams and highlight the interest of recent developments in the literature regarding the management control package.